Corporate Governance and Financial Performance: Evidence from Food and Beverage Firms Listed on the IDX - Abidah Dwi Rahmi Satiti; Rezza Adi Saputra; Dwi Hari Prayitno; Rizky Windar Amelia (CV. Ulil Albab Corp, 2026)
This study investigates the impact of corporate governance mechanisms on the financial performance of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2018–2023 period. Specifically, the analysis focuses on the independent board of commissioners, the board of directors, and the audit committee as key governance structures. The study population consists of 96 companies, from which 25 firms were selected using purposive sampling across six periods, yielding 150 firm-year observations. Data were analyzed using descriptive statistics, classical assumption testing, multiple linear regression, and hypothesis testing through t-tests and F-tests, with SPSS version 27 employed as the analytical tool. The empirical findings reveal that the independent board of commissioners has no significant effect on financial performance, the board of directors exerts a positive influence, while the audit committee demonstrates a negative effect. Furthermore, the governance variables jointly have a significant impact on financial performance. These results contribute to the corporate governance literature by providing sector-specific evidence from an emerging market context. The study also offers practical implications for managers, investors, and regulators, highlighting the importance of effective governance structures in enhancing firms’ financial outcomes Keywords: corporate governance, independent board of commissioners, board of directors, audit committee, financial performance